Risk Factors and Outcomes of Early Relapse After Curative Resection of Intrahepatic Cholangiocarcinoma - Yang, Hua; Wang, Jie; Li, Zehuan; Yang, Yi; Yang, Liuxiao; Zhang, Yong; Shi, Yinghong; Cao, Ya; Zhou, Jian; Wang, Zheng; Chen, Qing (Frontiers in Oncology, 2019)
Early recurrence after hepatectomy for intrahepatic cholangiocarcinoma (ICC) has a great effect on the long-term survival outcomes of patients. We conducted this study to identify risk factors for early recurrence and clarify whether early recurrence is related to ICC patients’ long-term survival outcomes. 322 ICC patients who underwent partial hepatectomy at Liver Cancer Institute of Zhongshan Hospital between January 2005 and December 2011 were included in this retrospectively study. Early recurrence was defined as ICC recurrence within two years after hepatectomy. We identified a total of 168 patients with early recurrence and 23 patients with late recurrence after hepatectomy. From the time of recurrence, the long-term survival outcomes were worse among patients who had early versus late recurrence (median OS 16.5 versus 44.7 months, respectively; P<0.0001). The overall survival of the early recurrence group was lower than that of the late recurrence group (P<0.0001). Multivariate Cox regression analysis demonstrated that multiple tumors (hazard ratio [HR], 1.951; 95% CI, 1.382-2.755; P< 0.001), lymph node metastasis (HR, 1.517; 95% CI, 1.061-2.168; P=0.022), and higher serum CA19-9 levels (HR, 1.495; 95% CI, 1.095-2.039; P=0.011) were independent risk factors of early recurrence. Moreover, multiple tumors (HR, 1.641; 95% CI, 1.120-2.406; P=0.011), lymph node metastasis (HR, 2.008; 95% CI, 1.367-2.949; P<0.001), elevated NLR (HR, 1.921; 95% CI, 1.331-2.774; P<0.001) and higher serum CA19-9 levels (HR, 1.990; 95% CI, 1.409-2.812; P<0.001) were independent predictors of overall survival for ICC patients with early recurrence. Collectively, our findings demonstrated that multiple tumors, lymph node metastasis, and higher serum CA19-9 levels were associated with the increased risks of early recurrence and worse prognoses of ICC after curative-intent resection.